Moral and religious motives in the works of J. R. R. Tolkien: cultural context - A. Y. Morozov, (Ukrainian Cultural Studies, 2017)
The main moral and religious themes of J. Tolkien`s novels “The Lord of rings” and “The Silmarillion” are observed in the article. It is analyzed that Tolkien followed Christian tradition, sharing st. Augustine`s conception of evil as the absence of good. It is clarified Tolkien`s anti-Nietzschean position where evil is equal to the will to power, while the good is associated with humility and serving. It is shown an author`s interpretation of Socratic classic inquiry: would people live virtuous life if they achieve omnipotence and why moral life is preferable than immoral one. According to Tolkien, human moral obligations are closely connected with the awareness of freedom and mortality which are regarded as a gift to a man, enabling to escape from senseless “bad infinity” (Hegel) of material determinant existence. In its turn, a notion of “gift” refers to metaphysical model of world that assumes divine being and his providential intervention in the course of earthly history. One of this divine providence`s manifestation is so called “eucatastrophe”, unexpected salvation from tragedy, therapeutic consolation that returns to a man the feeling of meaningfulness and joy of being. It is suggested that salvation can be interpreted in romantic way as coincidence point of trajectories of art and nature, where fairy tale embodies in life, and life starts to be built according to the laws of fairy tale.
Keywords: virtue, evil as absence of good ,will to power, death as a gift, providence, salvation